Animated Fairy Tale Learning Raises Preschool Language Achievement: Pembelajaran Dongeng Animasi Meningkatkan Prestasi Bahasa Anak Prasekolah - Nining Siti; Akhtim Wahyuni (Academia Open, 2025)
General Background: Language functions as a fundamental communication tool encompassing listening, speaking, reading, and writing skills in early childhood development. Specific Background: Observations in a kindergarten setting revealed that children aged 5–6 years demonstrated limited ability to answer questions, retell stories, and construct simple written sentences, indicating insufficient stimulation of language acquisition. Knowledge Gap: Although storytelling is widely applied in early childhood education, structured integration of animated fairy tale media within classroom-based action research to address multiple language indicators remains underexplored. Aims: This study aimed to increase language abilities of children aged 5–6 years through animated fairy tale learning activities conducted in classroom instruction. Results: Using Classroom Action Research based on the Kemmis and McTaggart model involving 13 children across pre-cycle, Cycle I, and Cycle II, the average language achievement increased from 38% in the pre-cycle to 52% in Cycle I and reached 76% in Cycle II, with 92% of children achieving mastery criteria. Improvements were observed in answering complex questions, retelling stories, and writing simple structured sentences. Novelty: This study presents a structured application of short-duration animated fable storytelling with forward plot sequences and interactive questioning as a classroom-based instructional intervention. Implications: The findings indicate that animated fairy tale learning provides an alternative pedagogical strategy for early childhood language instruction and supports development of listening, speaking, and early literacy competencies. Highlights: Short Animated Fable Storytelling Increased Mastery Rates From Total Non-Achievement to Dominant Completion Levels. Interactive Narrative Sessions Improved Children’s Ability to Reconstruct Story Content and Respond to Complex Questions. Sequential Classroom Cycles Demonstrated Progressive Growth in Early Writing Structure Formation. Keywords: Animated Fairy Tales, Early Childhood Language Achievement, Classroom Action Research, Digital Storytelling Media, Preschool Literacy Development